International non-state actors under the light of International Law: the case of transnational companies - López-Jacoiste Díaz, Eugenia (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
Transnational enterprises have never been as important as they are today. Their influence on the economic and political life of international society is undeniable. Its autonomous and unrestrained actions have been favored by the defense of almost absolute trade liberalization by the WTO. They have undoubtedly acquired an unprecedented role in the organization of international commercial interests. These facts do not correspond however to its deficient international legal status and even less to its much-discussed international subjectivity. Such enterprises are more than mere objects of the international order and they can even be derived or functional subjects of the international order, despite the doctrinal reluctance and inadequacies of international law.
Keywords: transnational enterprises; economic and commercial globalization; non-state actors; international legal capacity; subjects of international law